Formate diffusion engineering of hole transport layer for highly efficient N-I-P perovskite solar cells - Qu, Duo; Wang, Yi; Dong, Shuxin; Zhou, Bin; Wang, Chenhui; He, Zhenhua; Zhang, Xinyue; Liu, Feipeng; Tu, Yongguang (Materials today physics, 2022)
The dominant hole transport material in the state-of-the-art n-i-p perovskite solar cells (PSCs) mainly is Spiro-OMeTAD, which suffer from the instability issue caused by the intrinsic nature of additives and dopants. Here, a formate diffusion engineering of Spiro-OMeTAD is proposed to improve the stability and performance of PSCs. By adding a novel bis(trifluoromethyl)benzylamine formate into the Spiro-OMeTAD, both the conductivity and hole mobility of the Spiro-OMeTAD layer are enhanced. Results of ionic distribution profiling validate evidence of formate diffusion from the Spiro-OMeTAD layer into the perovskite bulk. The diffused formate could effectively reduce the interfacial non-radiative recombination of perovskite/Spiro-OMeTAD interface and adjust the interfacial energy level, thus enhancing the carrier extraction. This concurrent Spiro-OMeTAD engineering and surface passivation scheme renders higher efficiency in n-i-p PSCs. This formate diffusion strategy, which synergistically couples electrical property of hole conductor and defect passivation of perovskite layer, could open a route to develop high-performance optoelectronic devices. [Display omitted] •A formate diffusion strategy to improve performance of the Spiro-OMeTAD is proposed.•The conductivity and hole mobility of the Spiro-OMeTAD layer are enhanced.•The diffused formate could reduce the interfacial non-radiative recombination.•The regular n-i-p PSCs with large enhancements in efficiency and operational reliability.